The impact of tax law changes on bank dividend policy, sell-offs, organizational form, and industry structure - Hamid Mehran; Michael Suher (Federal Reserve Bank of New York, 2009)
This paper investigates the effect at the bank and industry level of a 1996 tax law change allowing commercial banks to elect S-corporation status. By the end of 2007, roughly one in three commercial banks had either opted for or converted to the S-corporation form of organization. Our study analyzes the effect of this conversion on bank dividend payouts. It also examines the effect S-corporation status has on a community bank's likelihood of sell-off and measures a firm's sensitivity to tax rates based on its choice of organizational form. We document that dividend payouts increase substantially after a bank's conversion to S status. Moreover, community banks that convert are significantly less likely to be sold than their C-corporation peers. We estimate a tax rate elasticity of conversion in the range of 2 to 3 percent for every 1-percentage-point change in relative tax rates. Overall, our results provide evidence that Subchapter S status has significant effects on bank conduct and industry structure.
Keywords: A12; K34; H25; G20; 330; Tax law; S corporations; organizational form; dividend policy; sell-offs; industry structure